INOVASI DAN DIFERENSIASI: STRATEGI BANK JATIM SURABAYA DALAM MENGHADAPI PERSAINGAN INDUSTRI PERBANKAN - Dewi Ayu Lestari; Rhenata Sabrina; Mayada Audi A R; I. A. Nuh Kartini (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine competitive strategies in the banking industry as well as efforts to improve service quality as part of the marketing strategy at Bank Jatim Surabaya. In facing competition, Bank Jatim Surabaya implements several strategies, including improving service quality, providing adequate and comfortable facilities and infrastructure, and applying marketing strategies by directly engaging in the field. The research method used is a qualitative descriptive approach, with data sources obtained through observation, interviews, and documentation. In-depth interviews were conducted with informants consisting of employees of Bank Jatim Surabaya. In addition, secondary data in this study were obtained from literature studies in the form of journals, scientific articles, and other references relevant to the research topic. The results of the study indicate that the strategies implemented by Bank Jatim Surabaya include innovation and improvement in service quality, among others through the provision of various products ranging from savings to financing tailored to customer needs, the delivery of professional services by offering the best solutions to customers’ financial problems, and efforts to minimize complaints by implementing services in accordance with standard operating procedures (SOP). In addition, the bank also carries out innovations in the field of technology. From a marketing perspective, Bank Jatim Surabaya markets its products by directly engaging in the field in order to build and strengthen relationships with customers. The main strategy of Bank Jatim Surabaya in facing competition in the banking industry focuses more on improving service quality and excellence, because customer satisfaction is one of the strategic factors to win the competition while maintaining the company’s image in the eyes of the public. Therefore, the quality of customer service becomes a very important aspect, since service is not merely about serving, but also includes the ability to understand, comprehend, and feel the needs of customers